2022
DOI: 10.1007/s00431-022-04445-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of family meals and food consumption in families at high risk of type 2 diabetes: the Feel4Diabetes-study

Abstract: A family meal is defined as a meal consumed together by the members of a family or by having ≥ 1 parent present during a meal. The frequency of family meals has been associated with healthier food intake patterns in both children and parents. This study aimed to investigate in families at high risk for developing type 2 diabetes across Europe the association (i) between family meals’ frequency and food consumption and diet quality among parents and (ii) between family meals’ frequency and children’s food consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…This profile is the one that presents the highest SWFoL and better eating habits in general. According to [ 52 ], eating habits, both of parents and children, have been positively associated with better food consumption patterns (greater consumption of fruits and vegetables, and a lower consumption of sweets). In our study, this occurred only in the case of mothers and fathers and in the consumption of vegetables and sweets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This profile is the one that presents the highest SWFoL and better eating habits in general. According to [ 52 ], eating habits, both of parents and children, have been positively associated with better food consumption patterns (greater consumption of fruits and vegetables, and a lower consumption of sweets). In our study, this occurred only in the case of mothers and fathers and in the consumption of vegetables and sweets.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the frequency of family meals is associated with children’s healthier food consumption [ 52 ]. There is an inverse relation between the frequency of family meals and body weight in parents and children.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, it has been found that European children from families at high risk of developing T2D have low frequency of family meals. 18 Besides, results of a large multicentred European study showed that children born to IR parents and at risk of T2D were more likely to have unhealthy dietary patterns. 19 Thus, assessing families at high risk of T2D who potentially have already unhealthy lifestyle behaviours could help to identify modifiable factors in the family meals' structure that can protect against overweight/obesity and to get a better insight into this specific population.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are not so many studies assessing the association between parental IR and children' IR. Recently, it has been observed that children from parents at risk of T2D have less family meals frequency (5) . Also, in a previous study with European data, it has been observed that children from parents at risk of T2D that already had IR were found to have higher odds of unhealthy lifestyle patterns (6) .…”
mentioning
confidence: 99%
“…Moreover, having IR and obesity during childhood could increase the risk of developing T2D (4) . Therefore, assessing those families that are already at risk of T2D could help to get a better insight of this specific population as children from these families already have worse lifestyle behaviours (6) and less family meals frequency (5) .…”
mentioning
confidence: 99%